THE LIFETIME EXTENSION OF CAR AXLES TYPES OF RU1 AND RUSH WHEELSET FREIGHT CARS, RESTORED BY THE METHOD OF PLASMA-ARC METALLIZATION OF THE NECK AND UNDER PARTS MANUAL - Zelenin, V. I.; Kavunenko, P. M.; Tysenkov, V. V.; Tepliuk, V. M.; Polishchuk, M. A.; Lebied, V. D.; Lipisii, V. I.; Bondariev, S. V.; Havrylov, S. A.; Olhard, N. T.; Cheburov, S. O. (Science and Transport Progress, 2009)
The restoration method for the journals and wheel seats of the freight wagon wheelsets by means of plasma-arc metallization is presented and the results of the bench fatigue tests with the advisable operation life of the axles restored are given.